2023
DOI: 10.1002/eji.202149702
|View full text |Cite
|
Sign up to set email alerts
|

CCR4+CD8+ T cells clonally expand to differentiated effectors in murine psoriasis and in human psoriatic arthritis

Abstract: Psoriasis is a chronic inflammatory skin disease with an autoimmune component and associated with joint inflammation in up to 30% of cases. To investigate autoreactive T cells, we developed an imiquimod‐induced psoriasis‐like inflammation model in K5‐mOVA.tg C57BL/6 mice expressing ovalbumin (OVA) on the keratinocyte membrane, adoptively transferred with OT‐I OVA‐specific CD8+ T cells. We evaluated the expansion of OT‐I CD8+ T cells and their localization in skin, blood, and spleen. scRNA‐seq and TCR sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…In this mouse model, it was shown that prolonged skin inflammation induced by imiquimod favors the activation of OT-I CD8 + T cells specific to the cutaneous self-antigen [65]. These cells had a CCR4 + phenotype and were found in peripheral blood and in an expanded pool of memory T cells in the spleen.…”
Section: T Cells In the Pathogenesis Of Psoriatic Arthritismentioning
confidence: 98%
See 2 more Smart Citations
“…In this mouse model, it was shown that prolonged skin inflammation induced by imiquimod favors the activation of OT-I CD8 + T cells specific to the cutaneous self-antigen [65]. These cells had a CCR4 + phenotype and were found in peripheral blood and in an expanded pool of memory T cells in the spleen.…”
Section: T Cells In the Pathogenesis Of Psoriatic Arthritismentioning
confidence: 98%
“…Sorted CCR7 + CD45RA − CXCR3 − cells from peripheral blood mononuclear cells (PBMCs) stimulated with αCD3/αCD28 beads were analyzed at different time points. On day 3, after T cell receptor (TCR) stimulation, all CCR4 − -enriched T CM cells shifted their phenotype to double positive CCR4 + CXCR3 + T CM , and at later time points a small fraction of cells that were single positive for CXCR3 and a fraction of cells with the T EM phenotype were detected [65].…”
Section: T Cells and Immunology Of The Skinmentioning
confidence: 99%
See 1 more Smart Citation